Konsep Mekanisme Pasar dalam Pemikiran Ekonomi Islam Ibn Taimiyah: The Concept of Market Mechanisms in Ibn Taimiyah's Islamic Economic Thought - A. M. Nur Atma Amir; Muslimin Kara; Rahman Ambo Masse (Litera Academica Publishing, 2025)
This study aims to provide a comprehensive description of the market mechanism concept in Ibn Taimiyah’s Islamic economic thought, examine the role of the state and the hisbah institution in maintaining market justice, and explore the relevance of his ideas to contemporary economic issues and their implications for the development of modern Islamic economics. This research employs a qualitative approach using the library research method, analyzing relevant primary and secondary sources. The findings reveal that Ibn Taimiyah had a profound understanding of market mechanisms, in which prices are naturally determined through the interaction of supply and demand without excessive intervention. The state, through the hisbah institution, plays a crucial role in preserving market stability and justice by enforcing business ethics and preventing harmful practices. Government intervention is justified only when market distortions lead to injustice. Ibn Taimiyah’s economic thought remains highly relevant to contemporary issues such as monopoly, inflation, wealth inequality, and the crisis of business ethics. Thus, his ideas offer a conceptual foundation for building an Islamic economic system that is just, ethical, and sustainable.